Purcutaneus Radiofrequency Ablation In Liver Tumor - Budi Tulaka; Bradley Jimmy Waleleng; Luciana Rotty (The Indonesian Society for Digestive Endoscopy, 2022)
Tumor ablation is a minimally invasive approach commonly used in the treatment of liver tumors. Over the last two decades, percutaneous radiofrequency ablation (RFA) has been widely used for primary tumors and small metastases, especially in the liver. Effective treatment of RFA can be accomplished by complete ablation of the tumor accompanied by a margin resection of at least 0.5 cm. One of the commonly used methods is percutaneous radiofrequency ablation. The overall and disease-free survival rate of RFA was found to be more effective than that observed with surgical resection. The success rate of RFA is highly dependent on the precision of tumor targeting, which is influenced by two main factors, such as electrode tip placement and angulation for electrode placement. In this literature review, we will discuss about percutaneous radiofrequency ablation.